BRAT1 - a new therapeutic target for glioblastoma - Haydo, Alicia; Schmidt, Jennifer; Crider, Alisha; Kögler, Tim; Ertl, Johanna; Hehlgans, Stephanie; Hoffmann, Marina E.; Rathore, Rajeshwari; Güllülü, Ömer; Wang, Yecheng; Zhang, Xiangke; Herold-Mende, Christel; et al. (Cellular and molecular life sciences, 2025)
Glioblastoma (GBM), the most malignant primary brain tumor in adults, has poor prognosis irrespective of therapeutic advances due to its radio-resistance and infiltrative growth into brain tissue. The present study assessed functions and putative druggability of BRCA1-associated ATM activator 1 (BRAT1) as a crucial factor driving key aspects of GBM, including enhanced DNA damage response and tumor migration. By a stable depletion of BRAT1 in GBM and glioma stem-like (GSC) cell lines, we observed a delay in DNA double-strand break repair and increased sensitivity to radiation treatment, corroborated by in vitro and in vivo studies demonstrating impaired tumor growth and invasion. Proteomic and phosphoproteomic analyses further emphasize the role of BRAT1’s cell migration and invasion capacity, with a notable proportion of downregulated proteins associated with these processes. In line with the genetic manipulation, we found that treatment with the BRAT1 inhibitor Curcusone D (CurD) significantly reduced GSC migration and invasion in an ex vivo slice culture model, particularly when combined with irradiation, resulting in a synergistic inhibition of tumor growth and infiltration. Our results reveal that BRAT1 contributes to GBM growth and invasion and suggest that therapeutic inhibition of BRAT1 with CurD or similar compounds might constitute a novel approach for anti-GBM directed treatments.
Gesehen am 15.10.2025